The Influence of Financial Literacy and Income Level on UMKM Financial Management (Case Study of Tanjung Pering Village, Nourth Indralaya Sub-District) - Utami Rahmanisa; Lukita Tripermata; Reny Aziatul Pebriani (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
Managing finances is managing wealth to generate profits and utilizing sources of capital to finance the business. Financial literacy is a person's knowledge or understanding of the basic concepts of finance in managing finances to make decisions. The level of income is a unit of level that comes from the income of profits generated from the sale of goods and services within a certain period of time. This study aims to determine the effect of financial literacy and income levels on MSME financial management in Tanjung Pering Village, North Indralaya District. This research uses a quantitative method with a descriptive research type. The sample of this study were 97 MSME actors. Data collection techniques in this study using a questionnaire. The proposed hypothesis was tested using multiple linear regression analysis, coefficient of determination, simultaneous, partial. Based on the results of the hypothesis, it shows that financial literacy and income levels have a positive and significant effect on MSME financial management. The results of the t test show a financial literacy value of 4.088 and an income level of 12.475, which has a positive and significant impact on MSME financial management in Tanjung Pering Village.